The sustainable development and social tourism (Eurasian Journal of Ecology, 2016)
Issue of sustainable development nowadays is very popular and is researched in different studies. During the 90s, the term of sustainability entered a discourse which started to direct the economic and political structures that constitute the present larger context of the tourism system, the industry and its development.This paper explains the concept of sustainability, its definitions and indicators and also deals with the ways in which the concepts of social tourism and sustainable tourism and sustainable development have become increasingly connected. Also further will be discussed the strong relationships between development of social tourism and the sustainable development according reports of European Union.
Keywords: sustainable development; sustainability indicators; tourism; social tourism.